Anti-nucleocapsid Antibody Response After Two Doses of CoronaVac® Among Healthcare Workers - Ayşin KILINÇ TOKER; Duygu ÇERÇİOĞLU ÖZDEMİR; Esma EREN; Ayşe TURUNÇ ÖZDEMİR; Azade KANAT; İlhami ÇELİK; İbrahim TOKER (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2022)
Introduction: The Coronavirus disease-2019 (COVID-19) pandemic that started over two years ago has led to high mortality and morbidity. Vaccine studies have been initiated worldwide to end the pandemic, and the CoronaVac® vaccine was first administered to healthcare workers at high risk of COVID-19 in Turkey. In our study, we aimed to investigate serum antibody levels after vaccination. Materials and Methods: Volunteer healthcare workers without COVID-19 disease who received two doses of CoronaVac® vaccine 28 days apart and were at least 14 days after the last dose of vaccine were included in this study. Assessment of antibodies against Severe acute respiratory syndrome-Coronavirus-2 (SARS-CoV-2) in blood samples from participants was performed using the Elecsys® anti-SARS-CoV-2 electrochemiluminescence immunoassay. Samples with a cut-off index (COI) (COI; signal sample/cut-off) <1.0 were considered negative; whereas samples with COI≥1.0 were deemed positive. Results: A total of 269 healthcare workers, 168 women (62.5%), were included in our study. The mean age of the participants was 37.7±8.6 (minimum-maximum: 21-62). Antibody levels were positive in 188 (69.9%) of the participants. The median antibody level was 9.2 COI (interquartile ranges=3-34.7). In terms of mean age, the mean age of participants with negative antibodies was higher with a statistically significant difference (p=0.001). The antibody positivity rate of women was higher than that of men (p<0.001). No statistically significant association was found between the time elapsed after vaccination, presence of comorbidities, development of post-vaccine side effects, and antibody levels. It was found that one or more side effects developed in 45.7% of the participants after vaccination. Conclusion: Our study showed that seropositivity developed significantly in healthcare workers after the CoronaVac® vaccine. It emphasizes the importance of maintaining infection prevention and control measures and administering the SARS-CoV-2 vaccine for healthcare workers at high risk.